Perception and Objective Being: Peter Auriol on Perceptual Acts and their Objects - Lička, Lukáš (American catholic philosophical quarterly, 2016)
This article discusses the theory of perception of Peter Auriol (c. 1280-1322). Arguing for the active nature of the senses in perception, Auriol applies the Scotistic doctrine of objective being to the theory of perception. Nevertheless, he still accepts some parts of the theory of species. The paper introduces Auriol's view on the mechanism of perception and his account of illusions. I argue for a direct realist reading of Auriol's theory of perception and propose that his position becomes clearer if we use the distinction between the first- and third-person perspectives that he seems to presuppose.